Shifting identities through switching codes: A close look at the social languages of pre-service English teachers in an Indonesian context - Dwi Riyanti (Indonesian JELT, 2017)
The globalization of English has undoubtedly brought shifts into how the English language is taught in classroom settings and how English teachers are prepared. In English as a foreign language (EFL) settings, for example, teaching and learning English is generally influenced by local contexts. Taking into account the sociocultural contexts of the learners and the teachers, identity construction becomes one important aspect in the process of English teaching and learning. Focusing on the microanalysis of social language uses, the study was aimed to understand how pre-service teachers of English as a foreign language in a multilingual setting, Indonesia, enact their identities through their language use in classroom settings. The data for this study was obtained from a classroom observation where an English pre-service teacher was performing peer teaching. The discourse analysis of the first thirteen minutes of a pre-service teacher's teaching demonstration indicates that multiple identities were enacted when the student teacher switched from one language to another. The pervasive use of code-switching in four different languages (Indonesian, English, Arabic, and Malay) provides clues that Mamas, a student teacher's pseudonym in the study was enacting different identities as he taught his peers. While further research is absolutely necessary to obtain more vivid pictures of the reasons behind using multiple languages in teaching English within this context, the study provides insight about how pre-service teachers in an Indonesian context try to develop identities as they learn to teach English.